Whole genome copy number analysis in search of new prognostic biomarkers in first line treatment of mantle cell lymphoma. A study by the LYSA group. Issue 4 (25th June 2020) - Le Bris, Yannick; Magrangeas, Florence; Moreau, Anne; Chiron, David; Guérin‐Charbonnel, Catherine; Theisen, Olivier; Pichon, Olivier; Canioni, Danielle; Burroni, Barbara; Maisonneuve, Hervé; Thieblemont, Catherine; Oberic, Lucie; et al.
Abstract: Mantle cell lymphoma (MCL) is a lymphoproliferative disorder characterized by the t(11;14)(q13;q32) CCND1/IGH translocation. This lymphoma is however extremely heterogeneous in terms of molecular alterations. Moreover, the course of the disease can vary greatly between indolent forms with slow progression and aggressive conditions rapidly pejorative. The identification of early markers allowing to predict individual patients outcome has however been unsuccessful so far. The LyMa trial treated homogeneously a cohort of young MCL patients. This appeared as a good opportunity to search for biomarkers of response to therapy. DNA extracted from diagnostic paraffin‐embedded lymph node biopsies from 100 patients with newly diagnosed MCL, homogeneously treated in this prospective clinical trial, were investigated for copy number alterations and copy neutral loss of heterozygosity using the Oncoscan SNP‐array scanning the whole genome. An independent confirmatory cohort was used to strengthen the possibly relevant anomalies observed. Here we describe the recurrent anomalies identified with this technique. Deletions of 17p( TP53 ) and 9p( CDKN2A ) were more frequent in refractory or early relapsing patients (10%), but had no significant impact in univariate analysis on progression‐free (PFS) or overall survival (OS). Regardless of the presence of TP53 or CDKN2A deletions, gains in 7p22 (8, 5%) were associated with better PFS in univariate but not in multivariate analysis including MCL International Prognostic Index and treatment. Gains of 11q( CCDN1 ), suggesting gains of the CCND1/IGH fusion, were associated with worse OS and PFS in univariate and multivariate analyses. This worse prognosis impact was confirmed by FISH in an independent confirmatory cohort. This work, using a whole genome approach, confirms the broad genomic landscape of MCL and shows that gains of the CCND1/IGH fusion can be considered as a new prognostic structural variant. Genomic abnormalities of prognostic impact could be useful to strengthen or de‐escalate treatment schedules or choosing targeted therapies or CART‐cells.